Efficacy of 1-week proton pump inhibitor triple therapy as first-line Helicobacter pylori eradication regime in Asian patients: Is it still effective 10 years on? - Qua, Choon-Seng; Manikam, J.; Goh, Khean Lee (Wiley-Blackwell, 2010)
OBJECTIVE: To re-examine the efficacy and tolerability of 1-week proton pump inhibitor triple therapy as a first-line Helicobacter pylori (H. pylori) eradication therapy. METHODS: Consecutive participants with a positive rapid urease test during an outpatient upper endoscopy were included. All participants were given pantoprazole 40 mg b.i.d., amoxycillin 1 g b.i.d. and clarithromycin 500 mg b.i.d. for 1 week. They were asked to return after 1 week to report any side effects related to the medications and to check for compliance. Successful eradication was defined by negative 13C-urea breath test at least 4 weeks after the completion of therapy. RESULTS: A total of 191 patients were recruited into the study, of whom 81 were male (42.4%) and 110 female (57.6%), with a mean age of 55.6 (range 21-88) years. Overall 26 patients (13.6%) defaulted follow up and five patients were not compliant (taking less than 85%) with the medications. Per-protocol and intention-to-treat eradication rates were 84.4% (95% CI: 78.6-89.9%) and 71.2% (95% CI: 64.5-77.6%), respectively. Overall 68 participants (42.5%) reported no side effects, followed by 58 (36.3%) with a taste disturbance, 16 (10.0%) with epigastric pain, 15 (9.4%) with diarrhea, 13 (8.1%) with nausea or vomiting, 12 (7.5%) with loss of appetite, nine (5.6%) with dizziness and two (1.3%) with an allergic skin rash, none of which was severe. CONCLUSION: The current regime using pantoprazole, amoxycillin and clarithromycin is highly tolerable and effective and should continue to be recommended as a first-line therapy for H. pylori eradication in our setting.